They Should Say "I Don't": Norms About Midpregnancy Marriage and Job Loss. Issue 2 (27th October 2016) - Gassman‐Pines, Anna; Gibson‐Davis, Christina M.; Vernot, Corey; Butler, Maggie; Hall, Natalie; Taylor, Lauren; Eastwood, Katherine; Zhang, Xinri
Abstract: This study examined effects of local economic conditions on individuals' attitudes toward midpregnancy marriages using an experimental vignette method. Adults ( N = 460) were each shown two vignettes about a hypothetical couple expecting a baby; within each vignette pair, vignettes randomly varied as to whether the couple lived in a community that had recently experienced job losses or had stable employment. Respondents indicated if the couple should and will get married before the baby's birth. Results showed that worse local economic conditions led people to believe that marriage would be less common. Among more socioeconomically disadvantaged respondents, if the hypothetical couple lived in a community with job loss, fewer respondents also thought that the couple should marry. In contrast, among more socioeconomically advantaged respondents, slightly more respondents thought that the couple should marry. When economic conditions worsen, low‐socioeconomic‐status individuals may believe that financial prerequisites for marriage become harder to meet.